Management of coastal biodiversity based on social-cultural values in constructing conservation character education - ABUBAKAR SIDIK KATILI; RAMLI UTINA; YOWAN TAMU; ELYA NUSANTARI (Biodiversitas Journal of Biological Diversity, 2018)
Katili AS, Utina R, Tamu Y, Nusantari E. 2018. Management of coastal biodiversity based on social-cultural values in constructing conservation character education. Biodiversitas 19: 1763-1768. Coastal biodiversity is quite high including coral reef, mangrove, seagrass, and fishery resources. Management of coastal biodiversity can be conducted interdisciplinary covering various aspects. Four main aspects can be integrated, i.e., physical-biodiversity, social-cultural, character education, and conservation. This present study aimed to describe: coastal biodiversity in Gorontalo Province, Indonesia community’s social-cultural value and local wisdom embodying conservation character of the coastal ecosystem, and character education of coastal ecosystem biodiversity in primary school by learning with a prototype of conservation character-based materials. Specifically, the present study aimed to construct the conservation character education based on social-cultural values. Data were analyzed with descriptive qualitative method by comparing and referring to findings from the previous studies. The procedure used in this research was four-D, i.e., (i) Define stage; by doing the identification and exploration of the coastal biodiversity potential. The methods used in this stage was exploration survey method. Focused group discussions were conducted with coastal communities to identify social-cultural values and local wisdom and to analyze the core and basic competence of learners by examining the tools of the lesson and determining the competence. (ii) Design stage; by designing a prototype of learning material to construct the conservation character for learners. (iii) Development stage; by validating the prototype of learning material for constructing the conservation character for the learner. (iv) Dissemination stage, by doing seminars and information dissemination on a prototype of learning material to construct the conservation character. The results showed that in Gorontalo, there were three components of the coastal ecosystem which included mangrove, seagrass, and coral reef. The communities in the coastal area of Gorontalo were prominent in their strengthened social-cultural roots taking the form of ecological awareness. The community in coastal area possessed local knowledge of the natural resources, e.g., plants and animals, and local attribution of such resources in the local language. The conservation character-education based on social-cultural values, specifically local wisdom, is the most appropriate education model to encourage the pattern of biodiversity coastal ecosystem management. Conservation character education was highly relevant to life-enhancing skills, based on the empowerment of skills and coastal biodiversity potential in each region.